Pantoprazole Decreases Cell Viability and Function of Human Osteoclasts In Vitro - Markus Prause; Claudine Seeliger; Marina Unger; Elizabeth Rosado Balmayor; Martijn van Griensven; Alexander Tobias Haug (Hindawi Limited, 2015)
Proton pump inhibitors (PPIs) are commonly prescribed drugs that decrease stomach acidity and are thus often used to treat gastroesophageal reflux disease and as a preventative agent for the adverse effects of nonsteroidal anti-inflammatory drugs on the stomach mucosa. In recently published literature, an association between proton pump inhibitor administration and increased fracture risk has been stated. In order to reveal the underlying pathomechanisms of these observations, the effects of pantoprazole, a representative of the proton pump inhibitors, on human osteoclasts in vitro were evaluated in this study. Osteoclasts were stimulated with increasing concentrations of pantoprazole ranging from 0 μg/mL to 10 μg/mL over a period of seven days. Cell viability and tartrate-resistant acid phosphatase (TRAP) activity assays were performed after 1 day, 3 days, and 7 days, respectively. Here, stimulated osteoclasts presented a significantly lower viability and TRAP activity than the negative controls. Osteoclast-specific gene expression was evaluated after seven days and revealed no significant differences between all samples. Overall, the bone degrading and resorptive function of osteoclasts is inhibited by the administration of proton pump inhibitors. While PPI-related fractures through "basic multicellular unit" dysfunction are unlikely, the underlying pathomechanism remains unknown.